Self Disclosure Perempuan Korban KDRT di Kabupaten Sikka - Mustafa, Intan (Indonesian Social Science Review, 2023)
Domestic violence (KDRT) is all forms of violence that is attempted by a person that results in physical, psychological, sexual and economic harm, including threats and deprivation of freedom in the household. The purpose of this study was to find out the inhibiting factors for victims of domestic violence in expressing the problems they faced, and from these inhibiting factors, it was then used to make a perspective study of interpersonal communication so that victims of domestic violence could express themselves. In this research, the researcher uses a qualitative approach with a case study method or approach, for the selection of research subjects using a purpose sampling technique. The interview technique used is an in-depth interview. The results of the study stated that closing oneself to victims of domestic violence is not an easy thing, there are many considerations that cause a person to close himself, such as; The fear of the victims of domestic violence on the conception of women who cannot take care of and maintain their household properly, mistakes in interpreting the meaning of belis or dowry for women who are still seen as representing men's power over women, and also threats for threats and pressures given by their husbands. For this reason, it is necessary to have openness in interpersonal communication, which is able to provide space and time for victims to share their problems. Kekerasan dalam rumah tangga (KDRT) merupakan seluruh wujud tindak kekerasan yang dicoba oleh seorang yang berdampak menyakiti secara raga, psikis, seksual serta ekonomi, termasuk pula ancaman, serta perampasan kebebasan dalam rumah tangganya. Tujuan dari penelitian ini adalah untuk mengetahui faktor penghambat korban KDRT mengungkapkan permasalahan yang dihadapi, dan dari faktor penghambat tersebut selanjutnya digunakan untuk membuat telaah persepktif komunikasi antarpersonal agar orbanKDRT dapat mengungkapkan diri. Dalam penelitan ini peneliti menggunakan pendekatan kualitatif dengan metode atau pendekatan studi kasus (Case Study), untuk pemilihan subjek penelitian menggunakan teknik purpose sampling. Teknik wawancara yang digunakan adalah wawancara mendalam (in-depth interview). Hasil penelitian menyebutkan bahwa menutup diri bagi korban kekerasan dalam rumah tangga bukanlah sesuatu yang mudah, banyak pertimbangan-pertimbangan yang menyebabkan seseorang itu menutup diri seperti; Ketakutan para korban KDRT pada kosepsi perempuan yang tidak bisa mengurus serta menjaga rumah tangganya dengan baik, kekeliruan dalam mengartikan makna belis atau mahar bagi perempuan yang masih dipandang mewakili kuasa laki – laki atas diri perempuan, dan juga ancaman demi ancaman dan tekanan yang diberikan oleh suami. Untuk itu perlu adanya keterbukaan dalam komunikasi antarpribadi, yang mampu memberikan ruang dan waktu kepada korban untuk mencurhakan persoalan yang dihadapi.